2014
DOI: 10.4103/1793-5482.136717
|View full text |Cite
|
Sign up to set email alerts
|

Ventriculoperitoneal shunting: Laparoscopically assisted versus conventional open surgical approaches

Abstract: Objectives:Ventriculoperitoneal shunting (VPS) is a mainstay of hydrocephalus therapy, but carries a significant risk of device malfunctioning. This study aims to compare the outcomes of laparoscopic ventriculoperitoneal shunting versus open ventriculoperitoneal shunting (OVPS) VPS-placement and reviews our findings in the pertinent context of the literature from 1993 to 2012.Materials and Methods:Between 2003 and 2012, a total of 232 patients underwent first time VPS placement at Beth Israel Deaconess Medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…5 , 8 , 10-13 Shunt malfunction is a common complication following VP shunt placement, with studies reporting pediatric VP shunt failure rates ranging 8%-16% within the first 30 postoperative days and between 22% and 58% within the first year of placement. [25][26][27][28][29][30][31][32] Several studies have reported decreased rates of shunt malfunction following laparoscopic VP shunt placement as compared to an open approach. 20 , 24 , 33 , 34 This has been attributed to less frequent extra-peritoneal positioning of the distal VP shunt catheter and improved visualization affording optimal catheter placement.…”
Section: Discussionmentioning
confidence: 99%
“…5 , 8 , 10-13 Shunt malfunction is a common complication following VP shunt placement, with studies reporting pediatric VP shunt failure rates ranging 8%-16% within the first 30 postoperative days and between 22% and 58% within the first year of placement. [25][26][27][28][29][30][31][32] Several studies have reported decreased rates of shunt malfunction following laparoscopic VP shunt placement as compared to an open approach. 20 , 24 , 33 , 34 This has been attributed to less frequent extra-peritoneal positioning of the distal VP shunt catheter and improved visualization affording optimal catheter placement.…”
Section: Discussionmentioning
confidence: 99%
“…The LOS for HCP was 7.73 days. Since HCP is a result of many brain disorders and it is difficult to measure LOS for it alone, and study by Nigim et al [ 13 ] showed that mean LOS was five days for primary HCP, while Khan et al [ 14 ] showed that the mean and median duration of hospital stay for patients was 11.7 days and five days, respectively, however, most of the cases were adults and were having many comorbidities, and also HCP was secondary to other brain problems like tumors. Our study was limited as we do not know how many of the shunt cases were complicated.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Nevertheless, in very complex cases, the use of an endoscopy assisted catheter placement can still be necessary to control for extensive intraabdominal adhesions that cannot be handled from extraperitoneally. [10] Given the actual rates of shunt dysfunction, and here especially abdominal dislocation, our cohort is not sufficiently large to draw conclusions based on statistical analysis. With the present series we aim to share our technique in a detailed way and demonstrate the feasibility and safety of this approach.…”
Section: Discussionmentioning
confidence: 99%